Teacher Educators and Response to Intervention: A Survey of Knowledge, Knowledge Base and Program Changes to Teacher Preparation Programs - Schwartz, Diane; Blue, Elfreda; McDonald, Mary; Pace, Darra (Journal of the American Academy of Special Education Professionals, 2009)
With the 2004 reauthorization of the Individuals with Disabilities Education Improvement Act (IDEIA), the definition of a specific learning disability was significantly altered. No longer is it required that a student demonstrate a discrepancy between ability and performance to receive educational support (Horowitz, 1999). With this in mind, researchers developed a survey designed to ascertain information about faculty knowledge and understanding of RtI, faculty knowledge base and the degree to which this mandate has affected their teacher education programs. This study reports the results of a web-based survey completed by 84 teacher educators from 70 colleges and universities in New York. The findings focus on faculty knowledge, knowledge base, and teacher training program changes relative to RtI. Implications for preparing teachers for today’s classrooms are also discussed.